The cost channel reconsidered : a comment using an identification-robust approach - Gabriel, Vasco J. (2010)
We re-examine the empirical relevance of the cost channel of monetary policy (e.g. Ravenna and Walsh, 2006), employing recently developed moment-conditions inference methods, including identification-robust procedures. Using US data, our results suggest that the cost channel effect is poorly identified and we are thus unable to corroborate the previous results in the literature.